2022
DOI: 10.1109/access.2022.3157340
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Allocation Techniques for Cognitive Radio Networks

Abstract: The remarkable growth in the demand for multimedia streaming over wireless networks is challenged by spectrum scarcity. To mitigate the effect of such a challenge, Cognitive Radio Networks (CRNs) were introduced as a promising technology since CRNs offer a great advantage to unlicensed users, also known as secondary users (SUs), by allowing them to opportunistically access the licensed bands when these bands are not used by their primary users (PUs). In this work, an LTE-based CRN is proposed with the objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…CRN has been presented as a solution to the inefficient use of radiofrequency [ 6 ]. Spectrum sensing is a key feature of CRN, and several studies have shown that cooperative spectrum sensing is the most widely utilized spectrum sensing technique for resolving the problem of interference from secondary users to main users [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…CRN has been presented as a solution to the inefficient use of radiofrequency [ 6 ]. Spectrum sensing is a key feature of CRN, and several studies have shown that cooperative spectrum sensing is the most widely utilized spectrum sensing technique for resolving the problem of interference from secondary users to main users [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%